Feasibility of a Computer Role-Playing Game to Promote Empathy in Nursing Students: The Role of Immersiveness and Perspective - Ma, Zexin; Huang, Kuo-Ting; Yao, Lan (Cyberpsychology, behavior and social networking, 2021)
Empathy is considered a cornerstone of high-quality health care and a required element of nursing education. Although computer role-playing games (CRPGs) are a promising tool to promote clinical empathy, little is known about how and why it is effective at improving empathy. The goal of the current study is to investigate the feasibility and effectiveness of a CRPG on nursing students' empathy with a focus on immersiveness and perspective. Results from a 2 × 2 (virtual reality [VR] vs. non-VR × patient's family's perspective vs. health care provider's perspective) between-subjects experiment ( = 69) showed that playing the game in VR (vs. non-VR) led to greater spatial presence and empathy. Moreover, playing from the health care provider's (vs. patient's family's) perspective elicited greater empathy. A moderated mediation effect was found, suggesting that users' attention allocation significantly mediated the effect of immersiveness on empathy in the patient's family's perspective condition. These findings show the feasibility of using a role-playing game for nursing education. Both theoretical and practical implications involving empathy training were discussed, along with suggestions for further research.